The use of computational models in the management and prognosis of refractory epilepsy: A critical evaluation. (October 2021) - Rigney, Grant; Lennon, Matthew; Holderrieth, Peter
Highlights: Computational modelling is a new tool that can improve the prognosis and management of refractory epilepsy. Models have predicted surgical outcomes and optimised surgical resection sites for patients with refractory epilepsy. In silico optimisation of surgical resection sites can improve seizure control postoperatively. Computational models should be explored for their ability to improve surgical outcomes in patients with refractory epilepsy. Abstract: Purpose: Drug resistant epilepsy (DRE) affects approximately 30 percent of individuals with epilepsy worldwide. Surgery remains the most effective treatment for individuals with DRE, but referral to surgery is low and only about 60 percent of individuals who undergo surgery experience seizure control postoperatively. The present paper evaluates the evidence for using computational models in the prediction of surgical resection sites and surgical outcomes for patients with DRE. Methods: We conducted a search in the Medline data base using the terms "refractory epilepsy", "drug-resistant epilepsy", "surgery", "computational model", and "artificial intelligence". Inclusion: original articles in English and case reports from 2000 to 2020. Reviews were excluded. Results: Clinical applications of computational models may lead to increased utilisation of surgical services through improving our ability to predict outcomes and by improving surgical outcomes outright. The identification and optimisation of nodes that are crucial for the genesis and propagation of epileptiform activity offers the most promising clinical applications of computational models discussed herein. Conclusion: Advances in computational models may in the future significantly increase the application and efficacy of surgery for patients with DRE by optimising the site and amount of cortex to resect, but more research is needed before it achieves therapeutic utility.